Detection‐based weighted H∞ LFC for multi‐area power systems under DoS attacks. Issue 12 (5th July 2019) - Cheng, Zihao; Yue, Dong; Hu, Songlin; Xie, Xiangpeng; Huang, Chongxin
Abstract : This study is concerned with resilient load frequency control (LFC) scheme design of multi‐area power systems with communication delay and aperiodic denial‐of‐service (DoS) attacks. First, to identify DoS attacks, a detection mechanism in the actuator side is proposed which is a time counter measuring the input delay. The identified DoS attacks are constrained by its upper bound of frequency and duration. When DoS attacks are identified, actuator switches to zero‐input strategy from hold‐input strategy. According to the switching control inputs, switched time delay system model is established to describe the attack influence on LFC system. Further, a criterion of preserving weighted H ∞ performance is derived by combining piecewise Lyapunov–Krasovskii functional method with switched system method. Based on the criterion, the resilient control gain is designed by solving a set of LMIs. Finally, numerical simulations are given to verify the validness of the attack detection based resilient LFC scheme.